PTU-095 Dried blood spot testing for hepatitis C in community pharmacy – interim reporting of a quasi-experimental study of effectiveness. (22nd June 2015) - Radley, A; Tait, J; Stephens, B; Dillon, J
Abstract : Introduction: Low diagnosis rates for Hepatitis C (HCV) mean untreated progressive disease and ongoing infection. Up to 40% of service users on opioid replacement therapy (ORT) from pharmacies are infected. Audit demonstrates that only 2.5% of this estimated population is treated per annum. Stigma, travelling distance, confidentiality concerns and a lack of awareness of how to access testing, have been identified as barriers. For the ORT patients pharmacies offering dried blood spot testing (DBST) may overcome these barriers. This study compares uptake of testing in pharmacies offering DBST with testing from established routes, in a population receiving ORT. Established routes included general practice testing, testing in secondary care, testing in specialist drug services and testing in 3rd sector organisations. Method: A quasi-experimental study design was used to compare non-randomly chosen intervention and control groups for access and uptake of DBST. Staff from 6 community pharmacies were trained to provide DBST and provided with a list of untested patients who could be invited to be tested. The list was constructed through a data linkage exercise joining the prescribing database for Tayside with the laboratory testing database using the community health index number (CHI). The pharmacies tested consenting patients during the last quarter of 2014. The primary outcome measure was the proportion of ORT service users accessing testing. Uptake was compared for patients accessing DBST in the 6 community pharmacies during the last quarter of 2014, compared to service users accessing HCV testing from any other service, for the 12 months of 2014. Results: A total population of 1, 339 patients were identified as being prescribed ORT in Dundee City of which 561 had no record of testing for HCV. During the 3 month period, 43 patients from the 6 community pharmacies accepted a DBST from a total of 143 eligible patients attending those pharmacies. Within the 561 eligible patients taking ORT across the whole of Dundee City, 75 patients were tested for HCV (30% Vs 13%). The OR for increased uptake of testing within the 6 pharmacies was 2.25 (95% CI 1.48 to 3.42, Z statistic = 3.81 p = 0.0001). The results from the DBST taken by the pharmacies showed 12 patients HCV+, 23 HCV negative, 7 DBSTs were not processed because of a missing ID number and 1 sample was a duplicate﻿. Conclusion: This initial evaluation of DBST in community pharmacies found that a greater proportion of ORT service users took up the offer of a test, compared to the offer of a test from a wider range of providers, over a longer time period. This study shows that DBST in community pharmacies is both a feasible and effective method. Disclosure of interest: None Declared.